2011
DOI: 10.4103/0256-4947.75773
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus in a Saudi community

Abstract: BACKGROUND AND OBJECTIVES:Quantifying the prevalence of diabetes mellitus is important to allow for rational planning and allocation of resources. Therefore, we designed this study to determine the prevalence of diabetes among Saudi nationals.DESIGN AND SETTING:A cross-sectional study among patients attending a primary care clinic in June 2009.PATIENTS AND METHODS:Patients were interviewed with structured questionnaires to determine the presence of diabetes by questioning for history of the disease, and charts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
259
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(282 citation statements)
references
References 16 publications
16
259
7
Order By: Relevance
“…In the Kingdome of Saudi Arabia, the prevalence of diabetes mellitus among people is high and represents a major clinical and public health problem [8]. KSA is now classified by the International Diabetes Federation (IDF) to be among the top 10 countries globally with the highest projected prevalence of diabetes in 2011 (16.2%) and 2030 (20.8%) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the Kingdome of Saudi Arabia, the prevalence of diabetes mellitus among people is high and represents a major clinical and public health problem [8]. KSA is now classified by the International Diabetes Federation (IDF) to be among the top 10 countries globally with the highest projected prevalence of diabetes in 2011 (16.2%) and 2030 (20.8%) [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, no statistical association was observed between type of diabetes and gender. Alqurashi et al [7] results showed the prevalence rates of type 2 diabetes to be higher among males (34.1% vs. 27.6% in females 27.6%, P < 0.0001). In contrast, a recent cross-sectional study conducted in northern Saudi Arabia showed lower prevalence of diabetes in males (42.5%) than females (57.5%) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Saudi Arabia has a high prevalence of diabetes (raw diabetes prevalence of 17.6%) [6]. Estimate of diabetes prevalence has been published previously [7][8][9]. The amount of healthcare expenditure dedicated to diabetes corresponded on average to 17% of the total health budget spent; the largest share to diabetes was Saudi Arabia who spent 24% of total healthcare expenditure [2].…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) According to a recent study, the prevalence of diabetes in Saudi Arabia is 34.1% in males and 27.6% in females. (3) While the prevalence among adults of the Arabic speaking countries as a whole range between 4%-21%, with the lowest being in Somalia and the highest in Kuwait. (4) The increase in income per capita and the accompanying shift in lifestyle to more sedentary activity with high fat diets and resultant obesity apparently underlie much of the increased prevalence of diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%